Use of Lateral Calcaneal Flap for the Reconstruction of Posterior Heel Defect (Journal of Bangladesh College of Physicians and Surgeons, 2020)
Soft tissue defect of the lateral malleolus and achilles tendon is very challenging for reconstruction due to the bony prominence and limited local tissue availability. The purpose of this study to describe our early experience of 30 patients treated with this flap for reconstruction of posterior heel defects with or without exposure of tendo-achilles. The study was conducted at department of plastic surgery, National Institute of Traumatology and Orthopedic Rehabilitation between 2015 to 2018. Twenty five patients (20 male and 5 females) with soft tissue defects over the posterior heel underwent reconstruction using a lateral calcaneal flap. The etiology is trauma in twelve patients, chronic ulcer in four and surgical wound dehiscence for repair of Tendo-Achilles in nine patients. Patients age range from 15 to 60 years (mean 35yrs) and follow up period ranged from 6 months to 2 years(mean 1 yr). All flaps had good perfusion and survived completely. In 3 cases there was partial loss of skin graft managed conservatively. The lateral calcaneal flap can be used safely to provide sensory skin coverage of posterior heel in single stageJ Bangladesh Coll Phys Surg 2020; 38(3): 116-120